On the nature and scope of reported child maltreatment in high-income countries: opportunities for improving the evidence base. (November 2013) - Jud, Andreas; Fluke, John; Alink, Lenneke R. A.; Allan, Kate; Fallon, Barbara; Kindler, Heinz; Lee, Bong Joo; Mansell, James; Puyenbroek, Hubert van
Abstract : Although high-income countries share and value the goal of protecting children from harm, national data on child maltreatment and the involvement of social services, the judiciary and health services remain relatively scarce. To explore potential reasons for this, a number of high-income countries across the world (Belgium, Canada, Germany, the Netherlands, New Zealand, South Korea, Switzerland and the United States) were compared. Amongst other aspects, the impact of service orientation (child protection- vs -family-services-orientated), the complexity of systems, and the role of social work as a lead profession in child welfare are discussed. Special consideration is given to indigenous and minority populations. The call for high-income countries to collect national data on child maltreatment is to promote research to better understand the risks to children. Its remit ranges well beyond these issues and reflects a major gap in a critical resource to increase prevention and intervention in these complex social situations. Fortunately, initiatives to close this gap are increasing.